The growth and nutrient uptake of invasive vines on contrasting riverbank soils. (30th April 2019) - Rashid, M. Harun; Uddin, Md Nazim; Sarkar, Animesh; Parveen, Mahfuza; Asaeda, Takashi
Abstract: This study sought to investigate the research question as to whether the growth and nutrient uptake of two invasive vines, Pueraria lobata and Sicyos angulatus, are affected by the heterogeneity of soil characteristics of two riverbank sites with different flooding regimes. Soil, individual ramets of P. lobata and S. angulatus plants were sampled monthly from quadrats set on homogenous stands from two riparian sites along Tama River, Japan for over a year. Soil nutrients, above‐ground (AGB) and below‐ground biomass (BGB), tissue nutrient, and nonstructural carbohydrate contents were estimated, and resource allocations to different organs were calculated. Flooding frequency directly affected the substrate characteristics of the sites; the frequently flooded site had coarser particle and less nutrient content. There were significant differences between the BGB and the AGB of both P. lobata and S. angulatus between the sites. However, the BGB:AGB ratio of these species were statistically similar regardless of the substrate conditions. Although the biomass of S. angulatus were much reduced in coarse habitat, the total amount of nutrient uptake by P. lobata was not affected by habitat the condition. Concentrations of total nitrogen, total phosphorus, and starch in root tissues of S. angulatus were less in frequently inundated soil. The results of this study suggest that inundation frequency directly affects the substrate condition of a riverbank habitat, which in turn affects plant growth, and invasive plant species growing in such habitat respond differently to substrate condition in terms of growth and nutrient uptake.